Endonasal Transpterygoid Surgery for Adult Mature Teratoma in the Sphenoid Bone. Issue 1 (January 2021) - Zhou, Yicui; Pan, Chunchen; Guo, Tao; Wang, Yinfeng; Zhao, Yi; Sun, Jingwu
Abstract : Abstract: Teratomas are germline tumors commonly composed of multiple cell types derived from embryonic germ cell layers. Teratomas in head and neck region are exceptionally rare and present during the neonatal and infantile period. We describe a male adult with a mature teratoma originating from sphenoid body. A 24-year-old male patient presented with left-sided intermitted headache and facial numbness. Radiographic imaging showed a 3 cm × 2.3 cm mass with heterogeneous density in the sphenoid region. The endoscopic sphenoid sinus opening surgery was performed through endonasal transpterygoid approach. The final pathologic diagnosis was confirmed as mature teratoma. The patient has been followed-up for 18 months without recurrence. We suggest endonasal transpterygoid approach could be an effective and safe treatment for patients with mature teratoma in the sphenoid bone.